3x - 5y - 4 = 0 and 9x = 2y + 7; solve it with elimination method.

There are two equations provided here.

3x – 5y – 4 = 0 or 3x -5y = 4 ……. (1).

9x = 2y + 7 or 9x -2y = 7 ……(2).

Now only focusing on eq. numbered 1 and 2 …

3x – 5y = 4………(1)

9x – 2y = 7 ……(2)

Multiply eq. (1) by 3, we get….

3 (3x – 5y = 4) or 9x – 15y = 12…… (3).

Now we can easily subtract (2) and (3) to get…..

9x – 2y = 7

– 9x – 15y = 12.

– +13 y = -5

Or we get 13 y = -5 or y = -5/13.

Now we substitute the value of Y = -5/13 in equation (1) we get the value of x.

3x – 5(-5/13) = 4

3x +25/13 = 4

39x + 25 = 52

Or 39x = 52 – 25

39x = 27

Or x = 27/39 = 9 / 13

So x = 9/13 and y = -5/13.

Was this answer helpful?

  
   

4.5 (54)

Upvote (80)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question